The Influence of Digital Competence and Technology Management on Teachers’ Innovation Behavior and Job Performance - Tara Fadhila Amatullah; Siti Amanah; Muhammad Sofwan (FINGER : Jurnal Ilmiah Teknologi Pendidikan, 2026)
Background: Ash-Shiddiqi School has integrated iPad-based technology into the learning process as part of its commitment to implementing digital transformation in education. In this context, the effective use of educational technology is not only determined by access to digital tools, but also by teachers' ability to manage technology and apply it innovatively. Therefore, this study was conducted to examine the influence of digital competence, technology management, and innovative behavior on teacher performance at Ash-Shiddiqi School.Aims: The objective of this research is to analyze the influence of digital competence and technology management on the innovative behavior and job performance of teachers and educators at Ash-Shiddiiqi Integrated Islamic School in Jambi.Methods: This research employs a quantitative methodology, with data gathered through the distribution and collection of questionnaires via Google Forms. The data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) to formulate a model that elucidates the relationships among the variables examined in the study.Results: The results of the study indicate that digital competence and technology management have a significant effect on innovative behavior but do not affect job performance.  However, innovative behavior has a positive effect on job performance.  The results of this study confirm that improving teacher performance is not only determined by the level of digital competence and technology management skills, but also by the extent to which these skills are manifested in innovative behavior in the educational process.Conclusion: This study concludes that job performance is influenced by the innovative behavior of teachers. However, it should be noted that there are many factors that influence this innovative behavior, such as digital competence and management technology, which enable teachers to use technology to generate creative ideas and solutions in their work.